Fonksiyonel Derecelen-dirilmiş İçi Boş Silindirlerde Sürekli Rejimde Sıcaklık Dağılımının Tamamlayıcı Fonksiyonlar Yöntemi İle Sayısal Çözümü - Pekel, Hakan; Yıldırım, Vebil (Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2015)
This study presents a numerical solution for the steady state hyperbolic heat conduction problem in radial direction as one-dimensional case for the thick walled hollow cylinders made of Functionally Graded Material (FGM). The simple power that accepted as the material changing function has been applied for the material properties such as thermal conductivity, density, and specific heat. The governing differential equation of the temperature distribution has been solved using Complementary Function Method (CFM) which is one of the initial value methods. The obtaining numerical results have been compared with the analytical results. The variation of the nondimensional temperature distribution has been investigated with the in-homogeneity parameter. The results have been demonstrated in the figure.

Bu çalışmada radyal doğrultuda Fonksiyonel Derecelendirilmiş Malzemeden (FDM) yapılmış kalın cidarlı içi boş silindirlerin tek boyutlu zamana bağlı olmayan ısı problemi sayısal olarak ele alınmıştır. Malzeme değişim fonksiyonu olarak kabul edilen basit kuvvet fonksiyonu (simple power) ısı iletkenliği, yoğunluk ve özgül ısı gibi malzeme özelliklerine uygulanmıştır. Sıcaklık dağılımını idare eden ikinci dereceden diferansiyel denklem başlangıç değerleri yöntemlerinden biri olan Tamamlayıcı Fonksiyonlar Yöntemi (TFY) ile çözülmüştür. Elde edilen sayısal sonuçlar analitik çözümlerle karşılaştırılmış, boyutsuz sıcaklık dağılımının inhomojenlik parametresiyle değişimi incelenmiştir. Sonuçlar grafik halinde sunulmuştur.

Conference Paper -- Theoretical and Applied Mechanical Turkish National Committee, 2015

Konferans Bildirisi -- Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2015